The application of computational fluid dynamics to vibratory finishing processes. Issue 1 (2017) - Mullany, B.; Shahinian, H.; Navare, J.; Azimi, F.; Fleischhauer, E.; Tkacik, P.; Keanini, R.
Abstract: Vibratory finishing processes are finding increased application in the finishing of high value metallic components. Despite the growth of these processes, few models exist to predict workpiece material removal variations and surface finish uniformity. This paper explores the potential of modelling the media as a continuum and utilizing commercial computational fluid dynamic (CFD) packages to predict local velocity and pressure fields around stationary workpieces. Predicted 2D velocity fields are compared to those measured via Particle Image Velocimetry. Initial insights are provided on how local media fields and the system's driving frequency combine to affect the resulting workpiece topography.